2020
DOI: 10.1590/0001-3765202020200548
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the Effect of Lonidamine by Quercetin in MCF-7 human breast cancer cells through downregulation of MMP-2/9 mRNA Expression

Abstract: Combination therapies are becoming increasingly important to develop an effective treatment in cancer. Lonidamine is frequently used in cancer treatment, but it's often preferred to be used in combination with other drugs because of its side effects. In the present study, the effi cacy of the combination of lonidamine with quercetin, a fl avonoid of natural origin, on human MCF-7 breast cancer cells was evaluated. The results showed that the combined use of the compounds signifi cantly increased cytotoxicity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Quercetin regulated the immunomodulatory function through the JAK/STAT1 signaling pathway, which was followed by the synergistic killing of breast cancer cells [ 42 ]. Quercetin could inhibit the proliferation and invasion of breast cancer cells by downregulating the expression of MMP2 and MMP9 [ 43 ]. Kaempferol suppressed proliferation and induced cell cycle arrest, apoptosis, and DNA damage in MDA-MB-231 cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin regulated the immunomodulatory function through the JAK/STAT1 signaling pathway, which was followed by the synergistic killing of breast cancer cells [ 42 ]. Quercetin could inhibit the proliferation and invasion of breast cancer cells by downregulating the expression of MMP2 and MMP9 [ 43 ]. Kaempferol suppressed proliferation and induced cell cycle arrest, apoptosis, and DNA damage in MDA-MB-231 cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, published studies revealed the inhibitory effect of quercetin on radical production and the expression of MMP [ 60 ]. Along with previous works, quercetin could reduce the expression of MMP-2 based on the suppression of nuclear factor-kB (NF-kB) [ 61 ] or modulation of superoxide dismutase (SOD) activity [ 62 ]. Several studies demonstrated that the quercetin compound found in plant extracts like Oenothera biennis [ 63 ] and Magnolia officinalis [ 64 ] can inhibit MMP-2 secretion and be used as an anti-aging agent.…”
Section: Discussionmentioning
confidence: 98%
“…In terms of antiallergy, quercetin alleviates the inflammatory response of allergic conjunctivitis by inhibiting the membrane-associated protein tyrosine kinase (Lyn) (Ding et al, 2020). In previous studies, the anti-tumor activity of quercetin was reported (Azeem et al, 2022), which inhibits tumor cell proliferation and downregulates tumor protein expression (Ozkan and Bakar-Ates, 2020;Song et al, 2020a). In vitro experiments showed that quercetin alone can induce apoptosis of 13 hepatocellular carcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin also potentially has anti-tumor properties (Tang et al, 2020). It inhibits the proliferation of colon cancer (Lin et al, 2020) and can downregulate the expression of MMP-2/-9 protein to restrict the hyperplasia of breast cancer cells named MCF-7 (Ozkan and Bakar-Ates, 2020). Song et al (2020a) found that the PI3K/Akt/mTOR signaling pathway could be blocked by quercetin for curing human prostate cell carcinoma PC-3 cells.…”
Section: Introductionmentioning
confidence: 99%